HUBUNGAN POWER LENGAN DAN KOORDINASI MATA TANGAN TERHADAP AKURASI LEMPARAN BOWLING PADA ATLET CRICKET PUTRI KOTA BEKASI - Hasan Basri; Gilar Wanda Pamungkas; Dindin Abidin (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2021)
Cricket is a sport that is played on a grassy field that leads to positive mental development and prioritizes honesty, fairness, honor / respect for others, accepts referee decisions, is polite and self-controlled. The cricket community at 45 Islamic University Bekasi is one of the places for student talent development in cricket, in this cricket sport has basic techniques including punches, catches, and throws. The method used in this research is the correlation research method. The result of this study is that there is a significant relationship between arm power and hand eye coordination on bowling accuracy both partially and simultaneously